Analysis of the Quality of the Physical Environment of the House on the Incidence of Tuberculosis in Tembalang Subdistrict - Vanessa Rizky Aditya; Mursid Raharjo; Onny Setiani (Jurnal Penelitian Pendidikan IPA, 2025)
Tuberculosis (TB) remains a major health problem in Indonesia, including in Tembalang Sub-district, Semarang City, which is listed as one of the areas with high cases. Indonesia ranks among the top three countries in the world with the highest number of TB cases exceeding one million cases. This research is an observational analytic study with a case-control study design. The purpose of this study was to assess the risk factors of household physical environment that affect the incidence of Tuberculosis in Tembalang Sub-district. The results showed that most of the houses with tuberculosis patients had unhealthy environmental conditions, such as poor air circulation (37.5%), high occupancy density (35%), improper flooring (57.5%), insufficient ventilation (67.5%), low lighting (85%), and high humidity (87.5%). These factors were found to have a significant association with an increased risk of TB. However, ceiling conditions and room temperature did not show a significant association with increased TB risk. These findings emphasize the importance of improving the living environment through education and community involvement in improving housing quality as a preventive measure to reduce TB transmission.